Alterations in neuromuscular function and perceptual responses following acute eccentric cycling exercise - Elmer, S. J.; McDaniel, J.; Martin, J. C. (European Journal of Applied Physiology, 2010)
Previous investigators have reported velocity-dependent strength loss for single-joint actions following acute eccentric exercise. The extent to which velocity influences recovery of multi-joint function is not well documented. Our main purpose was to compare alterations in maximal cycling power produced across a range of pedaling rates following eccentric exercise. An additional purpose was to determine the extent to which changes in rating of perceived exertion (RPE) associated with submaximal cycling reflect changes in maximal cycling power. Eighteen cyclists performed baseline trials of maximal and submaximal single-leg concentric cycling immediately before and 24 and 48 h after acute submaximal single-leg eccentric (151 ± 32 W, 487 ± 107 s) and concentric (148 ± 21 W, 488 ± 79 s) cycling trials. Maximum cycling power (apex of power-pedaling rate relationship; P max) was assessed using inertial-load cycling, and powers produced at 65, 110 and 155 rpm were also analyzed. Compared to baseline, P max was reduced (11-13%) at 24-48 h in the eccentric leg (P < 0.001). Power produced at 65, 110 and 155 rpm was reduced by similar relative magnitudes (11-15%) at 24-48 h in the eccentric leg. RPE increased (15-18%) at 24-48 h in the eccentric leg (P < 0.001). Magnitudes of relative changes in RPE did not differ from those for P max. There were no alterations in the concentric leg. Our results indicated a global, rather than velocity-specific, reduction in neuromuscular function. Such a global reduction does not support the notion of fiber-type specific damage from eccentric exercise. The similar relative changes in RPE and P max suggest that increased exertion may reflect the need to recruit additional motor units to produce the same submaximal power.